Zirconia microbial hollow fibre bioreactor for Escherichia coli culture - Liu, Lihong; Liu, Shaomin; Tan, X. (Elsevier Science Ltd, 2010)
Porous ceramic hollow fibre membranes can be used as bioreactors for microbe immobilization and growth. In this work, zirconia ceramic hollow fibre membranes were synthesised from 80 nm zirconia particles using a combined phase inversion and sintering technique The resulting membranes were characterised using SEM and XRD and tested for Escherichia coli immobilization. The membrane structural evolution with controlled E. coli growth was investigated. The well-maintained E. coli growth clearly shows that not only the hollow fibre lumen but also these micro-channels inside the fibre wall can be used as micro-bioreactors. Due to the unique structure properties, the prepared ZrO2 hollow fibre membranes can find wide applications in microbe immobilization system.